2014
DOI: 10.1075/lia.5.2.04rep
|View full text |Cite
|
Sign up to set email alerts
|

La production des scenarios contrefactuels par des apprenants adultes hispanophones

Abstract: The production of alternatives to factual events implies a counterfactual thinking in which reality is compared to an imagined view of what might have been. Previous studies in linguistics have analyzed counterfactuality in the context of conditional constructionsif P (then) Q(Bates 1976; Bloom 1981; Reilly 1982; Au 1983; Liu 1985; Bernini 1994; Chini 1995; Schouten 2000; Yeh & Gentner 2005). This article aims to describe the use of simple conditional sentences in a mutation task by 30 Spanish-speaking lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Crosslinguistic studies have shown that different languages might have different salient categories to express time, space, movement or irreality (Carroll et al 2008;Van linden and Verstraete 2008). In general, these differences lead L2 learners to explicitly replicate the salient categories of their L1 in their oral productions (Slobin 1996;Carroll et al 2012;Hung 2012;Repiso 2014). As avowed connoisseurs of metalinguistic issues, translators avoid overt transfers.…”
Section: Contrastive Linguistics and Translation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinguistic studies have shown that different languages might have different salient categories to express time, space, movement or irreality (Carroll et al 2008;Van linden and Verstraete 2008). In general, these differences lead L2 learners to explicitly replicate the salient categories of their L1 in their oral productions (Slobin 1996;Carroll et al 2012;Hung 2012;Repiso 2014). As avowed connoisseurs of metalinguistic issues, translators avoid overt transfers.…”
Section: Contrastive Linguistics and Translation Studiesmentioning
confidence: 99%
“…These authors have shown that there is no one single dedicated marker to encode counterfactuality across languages but rather a combination of elements that have other functions in other contexts (i.e., past-tense markers, aspectual markers, modal markers). In Spanish, the use of the perfect subjunctive is significantly higher compared to the combination of the past conditional and a modal marker (Repiso 2014). If the grammatical categories to express counterfactuality change from one language to another, the question arises whether translators replicate the source construction or use prominent constructions of the target language.…”
Section: Introductionmentioning
confidence: 99%